A user location and tracking system using wireless local area network and geographical information systems - Nishimori, Kent T. (Animo Repository, 2008)
The research developed an indoor user and location tracking system using Wireless Local Area Network signal strength and Geographical Information System. The signal strength was used to approximate the location of the user. With the additional knowledge of the floor plans of the building, the accuracy of the location and tracking system increased. This would fall under the researches on spatial problems and location sensing under ubiquitous computing. The research contributed as another variation to the indoor user location and tracking systems. The system incorporated Geographical Information Systems by applying the use of spatial information taken from a floor plan to increase its accuracy. This was achieved by eliminating computed positions that which the user is unable to pass due to walls and dividers and other obstacles that occupy that particular space. The error distance that the system has achieved was 3.79 meters on the average.